A regulatory element in the 3′‐untranslated region of CEBPA is associated with myeloid/NK/T‐cell leukemia. (29th November 2020) - Kimura, Yukiko; Iwanaga, Eisaku; Iwanaga, Kouta; Endo, Shinya; Inoue, Yoshitaka; Tokunaga, Kenji; Nagahata, Yousuke; Masuda, Kyoko; Kawamoto, Hiroshi; Matsuoka, Masao
Abstract: Objectives: CCAAT/enhancer‐binding protein α (CEBPA) is an essential transcription factor for myeloid differentiation. Not only mutation of the CEBPA gene, but also promoter methylation, which results in silencing of CEBPA, contributes to the pathogenesis of acute myeloid leukemia (AML). We sought for another differentially methylated region (DMR) that associates with the CEBPA silencing and disease phenotype. Methods: Using databases, we identified a conserved DMR in the CEBPA 3′‐untranslated region (UTR). Results: Methylation‐specific PCR analysis of 231 AML cases showed that hypermethylation of the 3′‐UTR was associated with AML that had a myeloid/NK/T‐cell phenotype and downregulated CEBPA . Most of these cases were of an immature phenotype with CD7/CD56 positivity. These cases were significantly associated with lower hemoglobin levels than the others. Furthermore, we discovered that the CEBPA 3′‐UTR DMR can enhance transcription from the CEBPA native promoter. In vitro experiments identified IKZF1‐binding sites in the 3′‐UTR that are responsible for this increased transcription of CEBPA . Conclusions: These results indicate that the CEBPA 3′‐UTR DMR is a novel regulatory element of CEBPA related to myeloid/NK/T‐cell lineage leukemogenesis. Transcriptional regulation of CEBPA by IKZF1 may provide a clue for understanding the fate determination of myeloid vs. NK/T‐lymphoid progenitors.